Laptops for seniors in easy steps : for all laptops with Window 11 - Vandome, Nick (In easy steps., 2025)
Laptops open up a world of possibilities, and you can use them anywhere! [This book] is your friendly guide to getting started and making the most of your laptop, especially mastering the key features of Windows 11. -- adapted from back cover